Adhesive wear and frictional performance of bamboo fibres reinforced epoxy composite - Nirmal, Umar; Hashim, Jamil; Low, K.O. (2012)
The aim of the present work is to investigate the adhesive wear and frictional performance of BMBFRE composite. Adhesive wear performance of BMBFRE composite was found to be superior for AP-O. The frictional performance of BMBFRE composite was found to be greater at low sliding velocity for AP-O by 44% relative to the high sliding velocity. The temperature differential of BMBFRE composite for AP-O to the sliding direction gave lower interface temperatures of about 31.4% and 13.2% as compared to R-O and P-O. The predominant wear mechanisms for AP-O was back film transfer associated with the formation of fine grooves on the worn surfaces. (C) 2011 Elsevier Ltd. All rights reserved.